2015
DOI: 10.1007/s10853-015-9361-x
|View full text |Cite
|
Sign up to set email alerts
|

Release and antimicrobial activity of levofloxacin from composite mats of poly(ɛ-caprolactone) and mesoporous silica nanoparticles fabricated by core–shell electrospinning

Abstract: Nanofibrous materials have often been reported as carriers for clinical drugs but face the limitation of releasing the drugs in a burst fashion during use. The aim of this study is to produce composite nanofibrous mats with sustained release, using the broad spectrum antibiotic levofloxacin (LVF) as a model. Sustained release was achieved through two approaches, i.e. by firstly loading LVF into mesoporous silica nanoparticles (MSN) and then incorporating the MSN in the core regions of poly(ecaprolactone) (PCL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…Silica nanoparticles have been very versatile to load different kinds of drugs and then embedded in electrospun polymers. These systems include PCL/silica nps with differents loaded drugs such as allantoin [57], levofloxacin [58], camptothecin [59], gentamicin [60]; also drug-loaded silica nanoparticles have been incorporated in Poly(L-Lactic acid) for doxorubicin release [61], poly(vinyl alcohol) for methylene blue release [62]. To incorporate drug-loaded silica nanoparticles into the electrospun matrix polymer is one of the main methods, but there are other systems of drug-loaded particles/polymer which are widely used in the electrospinning process, like bovine serum albumin (BSA) particles that were loaded with dexamethasone (DEX) and bone morphogenetic protein-2 (BMP-2) and then embedded in poly(caprolactone)-co-poly(ethylene glycol) copolymer, the dual-drug-loaded system was very effective to induce differentiation towards osteoblasts thanks to its synergistic effect of BMP-2 and DEX [63].…”
Section: Electrospun Nanoparticles/polymers Systems For Ddsmentioning
confidence: 99%
“…Silica nanoparticles have been very versatile to load different kinds of drugs and then embedded in electrospun polymers. These systems include PCL/silica nps with differents loaded drugs such as allantoin [57], levofloxacin [58], camptothecin [59], gentamicin [60]; also drug-loaded silica nanoparticles have been incorporated in Poly(L-Lactic acid) for doxorubicin release [61], poly(vinyl alcohol) for methylene blue release [62]. To incorporate drug-loaded silica nanoparticles into the electrospun matrix polymer is one of the main methods, but there are other systems of drug-loaded particles/polymer which are widely used in the electrospinning process, like bovine serum albumin (BSA) particles that were loaded with dexamethasone (DEX) and bone morphogenetic protein-2 (BMP-2) and then embedded in poly(caprolactone)-co-poly(ethylene glycol) copolymer, the dual-drug-loaded system was very effective to induce differentiation towards osteoblasts thanks to its synergistic effect of BMP-2 and DEX [63].…”
Section: Electrospun Nanoparticles/polymers Systems For Ddsmentioning
confidence: 99%
“…Furthermore, the average nanofiber diameter increased up to 529 nm in PVA-loaded MSNs electrospun mats as plotted through diameter distributions in Figure 3(c). This occurrence is due to the aggregation of MSNs in the polymer solution during electrospinning, rise in solution viscosity or incomplete dispersion during initial dispersion process into the polymer solution [6]. Figure 4(a) and (c), respectively.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…In order to overcome this problem, the encapsulating of the drugs in nanoparticles and incorporation of nanoparticles into random electrospun nanofiber has been employed. For instance, Jalvandi et al [6] reported approximately 70% of levofloxacin (LVF) in the nanoparticles was release in burst fashion throughout the first 20 min compared to 45% of LVF released from core shell nanofiber in the first day. Song et al [7] were studied designed a co-delivery system based on poly(lactic-co-glycolic acid)(PLGA) and nanoparticles for drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%
“…Jalvandi et al [ 79 ] loaded LV into mesoporous silica NPs (MSN), which were subsequently incorporated in the core region of PCL nanofibers via core–shell electrospinning. The antibiotic release from these fibres was more gradual than when released from PCL-LV and PCL-LV core-shell nanofibrous mats.…”
Section: Areas Of Applicationmentioning
confidence: 99%